Do demand for stocks associated with KLCI changes downward sloping from 1995 to 2004? - Khoo, Yong Lih (2004)
The result shows that the stock prices recorded positive abnormal returns for both inclusion and exclusion on the announcement day. In general, price effects for inclusion in both periods are considerably smaller magnitude than those for changes in the S&P500, and the Nikkei 500. The result also shows that the trading volume, on average, increase (decrease) for stocks added (deleted), on the announcement day.The temporary price effect for exclusion support price-pressure hypothesis in both periods. The price-pressure hypothesis also exists for inclusion in period 1995-2004. Inclusion in period 2000-2004 supports both the information hypothesis and the downward-sloping-demand-curve hypothesis. No evidence to support the liquidity hypothesis. In general, parametric test has better result than the non-parametric test for both abnormal price returns and abnormal trading volume measurement in this study. However, Generalized Sign Test, non-parametric test, in finding the cumulative average abnormal price, has better result than parametric test. In general, period 1995-2004 has better result than period 2000-2004 in trading volume effect for both inclusion and exclusion, and exclusion in price effect. However, for inclusion price effect in period 2000-2004 has better result than period 1995-2004